(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Ecdysone is a steroid hormone especially found in insects and mammals. One day old pupae of Tribolium castaneum were exposed to crude ecdysone at different concentrations of 10, 20, 40, 80, 160, and 320 μl/kg of whole wheat flour each for 1, 3 and 5 days. Adult recovery was significantly reduced in the treated pupae (F=3.47, P<0.01, df=7), and produced deformed individuals (F=39.29, P<0.001, df=7) at all exposure periods. The developmental time was similar in both the treated and untreated ones. The latent effect of the ecdysone treatment increased both the larval (F=4.26, P<0.001, df=7) and pupal (F=8.56, P<0.001, df=7) periods of the progeny reared on untreated foods. Similarly, the latent effect hampered recovery of the adult progeny (F=7.79, P<0.001, df=7) producing deformed individuals (F=2.65, P<0.05, df=7). Key words: Ecdysone; T. castaneum; Developmental period; Adult recovery. DOI: 10.3329/bjsir.v45i1.2213 Bangladesh J. Sci. Ind. Res. 45(1), 63-68, 2010